Mammadova, Rana - (:unkn) unknown (My University, 2026)
Rana Mammadova is a Senior Lecturer at the Department of Foreign Languages, Azerbaijan University of Architecture and Construction (AzUAC). She received her Bachelor's degree in English Language and Literature from Azerbaijan University of Languages in 2019 and her Master's degree in Linguistics (English Language) in 2023. Since 2024, she has been pursuing PhD studies in Theory of Language at the Azerbaijan National Academy of Sciences (ANAS). Her research interests include applied linguistics, English language teaching, language acquisition, discourse analysis, sociolinguistics, academic writing, and innovative approaches to foreign language education. She is the author of six scientific articles, one conference paper, and one curriculum programme. Before joining AzUAC in 2023, she worked as a translator and English language instructor.